Analysis Of The Adoption Of The Use Of The Indonesian Standard Quick Response Code (Qris) Using The Development Of The Technology Acceptance Model (Tam) In Msmes In Tarakan City - Arifin, Andry; Noviaristanti, Siska (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
In Tarakan City the increase in the number of QRIS users was followed by an increase in the number of QRIS merchants but did not reach the desired level. Recorded in the National Merchant Respository (NMRI) as much as 45.76% from the end of 2019 to June 2024. The purpose of this study is to analyze the use of QRIS for MSMEs in Tarakan City through the integration of the Technology Acceptance Model (TAM) model and the addition of other variables. The research findings indicate that Social Influence, Perceived Ease of Use, Perceived Trust, Perceived Value, and Intention to Use have a significant influence on the adoption of QRIS by MSMEs in Tarakan City. Conversely, Attractiveness of Alternatives, Perceived Security, and Perceived Usefulness do not show a significant direct influence on Intention to Use. These findings suggest that social encouragement, ease of use, trust, and perceived value are key factors in driving the acceptance of QRIS, while the attractiveness of alternatives and perceived security play a limited role in this context. This study provides practical implications for MSME actors and Bank Indonesia to enhance socialization, training, and trust in QRIS to achieve more optimal adoption targets